ISLAMIC EDUCATION IN MULNITHI AZIZSTAN MADRASA PATTANI SOUTH THAILAND - Hussam Dueramae; Azhar Arsyad; Sitti Syamsudduha; Muljono Damopolii (Universitas Islam Negeri Alauddin Makassar, 2020)
The main issue of this research is how the historical review of Islamic education in Mulnithi Azizstan Madrasa in Pattani-Southern Thailand. This type of research is a descriptive qualitative research that uses phenomenological, pedagogical, and psychological approaches. The researcher took the location in Mulnithi Azizstan Madrasa Pattani South Thailand. The findings showed that the early history of Islamic education in Pattani Thailand began in 1961 in the government of Sarit Tanarat by proposing a modernization program for Islamic boarding schools which was transformed into a private Islamic education school. After that policy, the growth of Islamic boarding schools is increasing rapidly. One of them is the Mulnithi Azizstan Madrasa. The concept of Islamic education institution in Mulnithi Azizstan Madrasa initially used the concept of Suffah in the time of its establishment. At present, the madrasa uses the concept of Halaqah and Majelis as the ways for students to learn. Finally, Mulnithi Azizstan Madrasa changed the learning system into each class.